1991
DOI: 10.1073/pnas.88.15.6878
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of intracellular calcium in Saccharomyces cerevisiae with an apoaequorin cDNA expression system.

Abstract: A method is described for measuring cytosolic free Ca2+ and its time-dependent changes in the yeast Saccharomyces cerevisiae by using the luminescent protein

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
93
1
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(102 citation statements)
references
References 34 publications
7
93
1
1
Order By: Relevance
“…However, we found that the introduction of a mid1⌬ mutation into the pgm2⌬ strain was unable to suppress the Ca 2ϩ homeostasis defects associated with the pgm2⌬ mutation. 2 Because both the rate of cellular Ca 2ϩ uptake and UPR induction are much larger in the pgm2⌬ mutant than was previously shown to be associated with the pmr1⌬ mutation (21,23), it is possible that the more robust CCE response observed in this strain is mediated by either the low affinity Ca 2ϩ uptake pathway or a combination of both.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we found that the introduction of a mid1⌬ mutation into the pgm2⌬ strain was unable to suppress the Ca 2ϩ homeostasis defects associated with the pgm2⌬ mutation. 2 Because both the rate of cellular Ca 2ϩ uptake and UPR induction are much larger in the pgm2⌬ mutant than was previously shown to be associated with the pmr1⌬ mutation (21,23), it is possible that the more robust CCE response observed in this strain is mediated by either the low affinity Ca 2ϩ uptake pathway or a combination of both.…”
Section: Discussionmentioning
confidence: 99%
“…Ca 2ϩ transport across the plasma membrane and its intracellular sequestration is tightly regulated such that the resting cytosolic Ca 2ϩ concentration is maintained in a range of 50 -200 nM (1)(2)(3)(4). Small variations in cytosolic Ca 2ϩ that occur in response to a number of stimuli are sufficient to activate a variety of Ca 2ϩ -sensing proteins, such as calmodulin and calcineurin.…”
mentioning
confidence: 99%
“…However, in spite of the similarity of the G protein-receptor signaling between S. cerevisiae and higher eukaryotes, it is still obscure whether the yeast G protein-receptor signal elicits a rapid [Ca 2+ ] i rise necessary for the early events in the mating pheromone response pathway (for review, see Davis, 1995). Only one laboratory thus far has reported a rapid increase in Ca 2+ influx followed by its efflux in response to the mating pheromone (Tachikawa et al, 1987), whereas other laboratories, including ours, have failed to detect such rapid Ca 2+ fluxes (Ohsumi and Anraku, 1985;Iida et al, 1990;Nakajima-Shimada et al, 1991;Prasad and Rosoff, 1992). This discrepancy could be due to differences in the methods used for detecting Ca 2+ fluxes.…”
mentioning
confidence: 97%
“…This discrepancy could be due to differences in the methods used for detecting Ca 2+ fluxes. To clarify this point unambiguously, we have employed the same method and yeast strain as those used by the laboratory reporting the rapid Ca 2+ flux (Tachikawa et al, 1987) and compared the results with those obtained under various experimental conditions using a [Ca 2+ ]i-monitoring system which we have established by using recombinant aequorin as a Ca 2+ -specific probe (Nakajima-Shimada et al, 1991). The present data show no evidence of rapid changes in Ca 2+ fluxes and [Ca 2+ ]i within about 15 min after the addition of α-factor, supporting the hypothesis that there is no Ca 2+ signal in the early stage of the yeast pheromone response pathway.…”
mentioning
confidence: 99%
“…Mating pheromone causes G 1 arrest and resumption of cell cycle progression by facilitating Ca ext 2ϩ influx, which results in calmodulin activation of calcineurin (1,(22)(23)(24)(25). Pheromone-induced Ca ext 2ϩ influx is mediated by Cch1p and Mid1p, which are plasma membrane proteins that by genetic criteria function as a single Ca 2ϩ uptake system (26 -29).…”
mentioning
confidence: 99%